Effects of topography on particle composition of 2011 tsunami deposits on the ria-type Sanriku coast, Japan. (15th October 2017) - Goto, Tomoko; Satake, Kenji; Sugai, Toshihiko; Ishibe, Takeo; Harada, Tomoya; Gusman, Aditya Riadi
Abstract: A geological survey was conducted in a small valley along the Sanriku coast, and the grain compositions of both autochthonous gravels and the 2011 tsunami deposit from the Tohoku-oki earthquake were investigated to reveal the depositional form of the tsunami deposits on the ria-type coast. The features of autochthonous gravels in the beach, riverbed, and slope areas are characterized by a combination of their rock type and roundness. The roundness values of the beach and slope gravels are large (0.8–0.9) and small (0.1–0.2), respectively, regardless of rock type, and the riverbed gravels are typically granite rocks with an intermediate roundness (0.4–0.5). The 2011 tsunami deposits along the survey transect include the above autochthonous gravels and show several characteristic features, such as a sharp erosional contact with the underlying peaty soil, normal and/or inverse grading structures, mud sheets, and richness in gravels in the lower unit, while the thickness shows no systematic changes with the distance from the coast. The presence of slope gravels suggests high tsunami inundation and flux, which eroded bare rock and talus and transported them to the valley plain by backwash current. The mixture of beach and riverbed deposits implies the formation of both an upstream current from the beach, which transported beach pebbles inland, and a backwash current along the channel, which accumulated sub-angular riverbed gravels around the river mouth. The characteristics of the 2011 tsunami deposit on the Sanriku coast, where narrow valleys are surrounded by high cliffs with steep slopes, are significantly different from those of sandy tsunami deposits in Sendai Plain, where a flat plain develops within several kilometers of the coastline. The differences among sedimentary facies are affected by the topography and autochthonous deposits.